Bruner's Stages of Thinking in 2nd Grade Students: A Case Study on Homework - Novi Asmarani Kusuma Dewi; Berliana Henu Cahyani; Yuyun Yulia (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
Bruner's stage of cognitive development is an alternative to knowing the characteristics of students other than Piaget's. It is hoped that teachers can find out the characteristics of students in thinking to prepare learning strategies that adjust to the characteristics of these students. For this reason, this research aims to describe Bruner's stages of thinking in grade 2 elementary school students on the theme of Caring for Animals and Plants. This research uses a qualitative approach with a single subject. The subjects in this study used a purposive technique, namely one 2nd-grade elementary school student. The instrument used in this study was the researcher as the main instrument and supported by documents of students' homework answers. Data analysis used descriptive techniques with data reduction steps, data presentation, and conclusion. The results showed that subject K used the stages of enactive and iconic thinking, while the stages of symbolic thinking were not carried out. For this reason, the teacher in giving problems is expected not to conflict with real life, and the issues faced by students must be seen clearly so as not to cause multiple interpretations by students.